Perinatal management of enlarged bronchogenic cyst causing hydrops fetalis. (2021) - Arnaoutoglou, Christos; Spyrakos, Spyros; Kapetanaki, Anastasia; Keivanidou, Anastasia; Machairiotis, Nikolaos; Zarogoulidis, Paul; Tsakiridis, Kosmas; Ioannidis, Aris; Saroglou, Maria; Tryfon, Stavros; Tsigaras, Georgios; Papaioannou, Georgios Konstantinos
Abstract: Bronchogenic cysts are rare congenital anomalies that they are usually diagnosed prenatally during the routine second trimester scan. We present such a rare case of bronchogenic cyst in a fetus. Our initial scan demonstrated a big cystic mass, which enlarged progressively causing shifting of the mediastinum and compression of the fetal heart. Consequent hydrops fetalis was treated with thoracoamniotic shunt and the pregnancy continued with no further complications. Pontnatal period, surgery and long term follow-up was uneventful.